Plasma Urate and Parkinson's Disease in Women - O'Reilly, Éilis J. (Oxford University Press, 2010)
Plasma urate has been consistently associated with a lower risk of Parkinson's disease in men, but it is less clear if this relation exists in women. Between 1990 and 2004, the authors conducted a nested case-control study among participants of the female-only Nurses’ Health Study. In controls (n = 504), plasma urate was positively associated with age, body mass index, alcohol consumption, hypertension, and use of diuretics and was inversely associated with physical activity and postmenopausal hormone use, as expected. Mean urate levels were 5.04 mg/dL for cases (n = 101) and 4.86 mg/dL for controls (P = 0.17). The age-, smoking-, and caffeine-adjusted rate ratio comparing women in the highest (≥5.8 mg/dL) with those in the lowest (<4.0 mg/dL) quartile was 1.33 (95% confidence interval: 0.69, 2.57; P(trend) = 0.4). Further adjustment for body mass index, physical activity, history of hypertension, and postmenopausal hormone use did not change the results. Unlike in men, these findings do not support the hypothesis that urate is strongly associated with lower rates of Parkinson's disease among women.